Expression, Purification And Quantitation Of Hemagglutinin-Neuraminidase For Dose-Ranging Assessment Of A Recombinant Protein-Based Newcastle Disease Subunit Vaccine - Lye, Ping Ying (2020)
Recombinant hemagglutinin-neuraminidase (HN) based subunit vaccine, which is non-infectious and can be produced using insect cell-culture systems, is a potential alternative to conventional live and inactivated Newcastle disease (ND) vaccines. However, process development for manufacture and efficacy assessment of HN based subunit vaccines has been hampered by the absence of reference standards, a cornerstone for robust and sensitive quantitative analytical methods. In this work, a downstream purification strategy was developed to obtain NDV HN which was expressed with a hexa-histidine fusion tag (rHN) to facilitate detection using generic antibodies. Highly purified rHN (~95%) attained after detergent extraction and two-stage ion-exchange-hydroxyapatite column chromatography was subsequently utilized as reference standards for quantitative ELISA development. The calibration curve for the developed ELISA was found to be linear between the range of 15.6‒1000 ng mL−1. The intra- and inter-assay precision expressed as a coefficient of variation (CV) were less than 10% and 12% respectively. Recovery of rHN at different stages of purification was monitored. Quantitation of rHN from crude cell lysates was subsequently performed for dose-ranging antibody response and protective efficacy studies. A higher dose (1500 ng) of rHN was correlated to a significant reduction in virus shedding and attainment of herd immunity, as indicated by a higher proportion of chickens (92%) with hemagglutination inhibition (HI) antibody titers ≥log23.